English Teacher Strategies in Writing Activities at the Eighth Grade of Junior High Schools at Kembayan Sub-district - Megista, Hilda; Yuliana, Yohanes Gatot Sutapa; Sumarni; Apriliaswati, Rahayu; Rezeki, Yanti Sri (Kirana Publisher (KNPub), 2023)
This research aims to describe the English teachers’ strategy in writing activities at the eighth grade of Junior High Schools at Kembayan sub-district and how the English teachers implement the strategy. This research used a descriptive qualitative design. The data were gathered from observation, interviews, and documentation. The result of this research showed that there were four teachers’ strategies for writing activities in the eighth grade. The strategies were guided writing strategy, repeating strategy, cooperating with peers strategy, and translation strategy. In implementing the teaching strategy, the English teacher asked the students to write some expressions and dialogues depending on the strategy used. The teacher who used the repeating strategy asked students to copy the expressions or dialogues in the textbook into their workbooks. For the translation strategy, the teacher asked students to translate expressions or dialogues and then asked them to write the translation in the workbook. For the guided writing strategy, the teacher wrote a dialogue on the whiteboard and asked students to write a dialogue using the random words given by following the template on the whiteboard. For the cooperating with peers strategy, the teacher asked students to discuss in a group and then write a dialogue. These strategies could help teachers in teaching students and also encourage students to participate in the teaching and learning process actively.